2017
DOI: 10.3847/1538-4357/aa831d
|View full text |Cite
|
Sign up to set email alerts
|

The Supernovae Analysis Application (SNAP)

Abstract: The SuperNovae Analysis aPplication (SNAP) is a new tool for the analysis of SN observations and validation of SN models. SNAP consists of an open source relational database with (a) observational light curve, (b) theoretical light curve, and (c) correlation table sets, statistical comparison software, and a web interface available to the community. The theoretical models are intended to span a gridded range of parameter space. The goal is to have users to upload new SN models or new SN observations and run th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…But while the availability of time-domain data has improved significantly, publicly accessible models of transients have remained elusive (we are aware of one other service that offers conditional public access to supernova models, SNAP, Bayless et al 2017). Individual works have focused on small subsets of data, offering descriptions of either light curve shapes or distributions of physical parameters for a given set of transients, but the specific data products depend heavily on the scientific motivations of the study in question.…”
Section: Introductionmentioning
confidence: 99%
“…But while the availability of time-domain data has improved significantly, publicly accessible models of transients have remained elusive (we are aware of one other service that offers conditional public access to supernova models, SNAP, Bayless et al 2017). Individual works have focused on small subsets of data, offering descriptions of either light curve shapes or distributions of physical parameters for a given set of transients, but the specific data products depend heavily on the scientific motivations of the study in question.…”
Section: Introductionmentioning
confidence: 99%
“…We also had access to the Supernova Analysis Application (SNAP) database (Bayless et al 2017), which currently contains several hundred observed SNe from space and ground observations 2 . However, the SNPhotCC dataset has several advantages over SNAP for this area of research.…”
Section: Datamentioning
confidence: 99%
“…They will be able to follow the evolution of the SN as the energy output shifts into the optical. From the time-resolved multi-wavelength data of the SBO curves, we will constrain the radii, ejecta mass, explosion energy, and density profile (Bayless et al, 2017).…”
Section: Sbo Of Ccsnementioning
confidence: 99%